The Internal and External Effects of Offshoring on Job Security - Zouheir El-Sahli; Joakim Gullstrand; Karin Olofsdotter (Lund University, School of Economics and Management, Department of Economics, 2017)
In this paper, we investigate the effects of offshoring on workers' job security using matched employer-employee data from Sweden. For our observed period (1997-2011), while the share of firms engaged in offshoring fell during the period from around 25% to 22%, offshoring per worker within offshoring firms almost doubled. We make use of this variation to contribute to the literature on several fronts by examining both the internal (i.e., firms' own offshoring activities) and the external (i.e., neighboring firms' offshoring activities) effects of offshoring on workers' employment spells. To deal with potential endogeneity, we use instruments based on world supply shocks for both the internal and external measures of offshoring. Our results suggest that external offshoring has a greater impact on job security than internal offshoring. In addition, having a university degree, being young, and being new to the job all reduce the risk of a job exit due to increased external offshoring. This result is indicative of a Schumpeterian job restructuring effect of offshoring, where old jobs are replaced by newer ones. Finally, the increased risk of a job exit from external offshoring is limited to workers in small firms that do not offshore themselves, suggesting a higher vulnerability of these firms to local shocks.
Keywords: F16; F66; J64; 330; offshoring; heterogeneous firms; job security; globalization